Demographic Analysis of Ophthalmic Surgeries in a Tertiary Care Center in Khyber Pakhtunkhwa, Pakistan: Demographic Analysis of Ophthalmic Surgeries in a Tertiary Care Center - Ahmad, Shahzad; Tariq, Hammad; Rehman, Aftab Ur; Saleem, Shafaq; Zaman, Arsala; Mahsood, Yousaf Jamal (Pakistan Journal of Health Sciences, 2025)
Different age groups and genders have unique needs when it comes to eye surgeries. Understanding these trends can help improve eye care services in resource-limited areas. Objectives: To study the types of eye surgeries performed in a tertiary care center in Khyber Pakhtunkhwa, Pakistan, and examine their link to age and gender. Methods: This retrospective observational study reviewed records of 3,016 patients. Data on age, gender, and procedures were analyzed using Chi-square tests, with p<0.05 considered significant. Results: The most common surgeries were intraocular lens (IOL) implantation (18.0%), primary repair surgeries (12.0%), phacoemulsification (11.6%), and extracapsular cataract extraction (10.4%). Older patients mostly underwent cataract-related surgeries, while younger patients had intraocular lens implantation and squint correction. Male patients had more cataract surgeries, while females had more primary repair surgeries. Conclusions: It was concluded that significant associations between age, gender, and surgical procedures were found, underscoring the need for more focused resource allocation and easier access to ophthalmic care, especially for women and older adults.